2019
DOI: 10.1002/1878-0261.12501
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and promoter methylation of angiogenic and lymphangiogenic factors as prognostic markers in melanoma

Abstract: The high mortality rate of melanoma is broadly associated with its metastatic potential. Tumor cell dissemination is strictly dependent on vascularization; therefore, angiogenesis and lymphangiogenesis play an essential role in metastasis. Hence, a better understanding of the players of tumor vascularization and establishing them as new molecular biomarkers might help to overcome the poor prognosis of melanoma patients. Here, we further characterized a linear murine model of melanoma progression and showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…For example, metastatic cutaneous melanomas were characterized by higher intratumoral and peritumoral LVD when compared to non‐metastatic tumors 287 . This is in line with the observation that the overexpression of VEGF‐C and ANG2 correlated with a poorer prognosis in melanoma patients 288,289 . In addition, a multivariate risk analysis conducted on primary tumors and sentinel LN biopsies from 45 melanoma patients revealed that the lymphatic vascular area of primary melanomas was an extremely sensitive and specific prognostic marker for the occurrence of tumor‐draining LN metastasis and could predict the metastatic phenotype more accurately than measurements of tumor thickness measuring 290 .…”
Section: Prognostic Value Of Tumor‐infiltrating Lymphatic Vesselssupporting
confidence: 82%
“…For example, metastatic cutaneous melanomas were characterized by higher intratumoral and peritumoral LVD when compared to non‐metastatic tumors 287 . This is in line with the observation that the overexpression of VEGF‐C and ANG2 correlated with a poorer prognosis in melanoma patients 288,289 . In addition, a multivariate risk analysis conducted on primary tumors and sentinel LN biopsies from 45 melanoma patients revealed that the lymphatic vascular area of primary melanomas was an extremely sensitive and specific prognostic marker for the occurrence of tumor‐draining LN metastasis and could predict the metastatic phenotype more accurately than measurements of tumor thickness measuring 290 .…”
Section: Prognostic Value Of Tumor‐infiltrating Lymphatic Vesselssupporting
confidence: 82%
“…The murine model of melanoma progression has been previously described [ 6 , 7 , 8 , 10 , 11 , 12 , 13 , 14 ] and comprises spontaneously immortalized nonmalignant melanocytes (melan-a) [5] and 3 cell lines with increasing malignant potential (4C, 4C11- and 4C11+) derived from melan-a following sequential cycles of forced anchorage impediment. Briefly, anoikis -resistant yet still nontumorigenic cells (named 4C) were obtained after subjecting melan-a melanocytes to 4 cycles of de-adhesion/adhesion.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the aforementioned in vivo models, there is a panoply of other animal species that can be used to study melanoma. A relevant model is the chicken chorioallantoic membrane that consists of a highly vascularized extra-embryonic membrane [278,297]. The good visibility, accessibility, and cost-effectiveness of this model turns it a suitable candidate for evaluating cancer biology as well as performing HTS in vivo.…”
Section: Other Animal Modelsmentioning
confidence: 99%